Sakaling malimutan kita - Gentolizo, Ivan Jon V.
Sakaling Malimutan Kita is a drama centered on Angelo as he undergoes a journey of healing by returning for the last time to see his estranged father, Mando, who recently passed away. Through this passage, the film places the main character in an emotional turmoil of also going back to the memories that he last shared with his father as he finally moves forward from the pain caused by the unexplained absence of Mando in his life. Utilizing a fragmented structure and the theory of 'Reconstructive memory', the film places the audience in the unreliability of memories and how the perceived truth based on a memory created through pain, clashes with the truth that is supported by a tangible proof.